Polymer-Bound Antioxidants: A Review of Discovery, Synthetic Strategies, and Characterization Methods - Sheikh, Mr, Mudassir; Verma, Mr. Ashish (American Journal of Biomedicine and Pharmacy, 2026)
In order to combat the physical loss (volatility and leaching) of conventional additives, this study investigates the identification, synthesis, and characterization of polymer-bound antioxidants. These materials are permanently stabilized by covalently attaching active moieties, like phenolic, amine, or natural polyphenol groups, to macromolecular backbones through reactive extrusion, grafting, or direct polymerization. While radical scavenging assays (DPPH/ABTS) demonstrate intact bioactivity, FT-IR, NMR, and TGA characterization validates chemical integration and improved thermal stability. The findings point to a trend toward environmentally benign, non-migratory stabilizers that are necessary for long-term durability in biomedical applications, active food packaging, and high-performance rubbers. Oxidative degradation, which is brought on by heat, light, and mechanical stress, is a constant danger to the durability of both natural and manmade polymers.